Exploring the bone marrow micro environment in thalassemia patients: potential therapeutic alternatives - Li, Zengzheng; Yao, Xiangmei; Zhang, Jie; Yang, Jinghui; Ni, Junxue; Wang, Yajie (Frontiers in Immunology, 2024)
Genetic mutations in the β-globin gene lead to a decrease or removal of the β-globin chain, causing the build-up of unstable alpha-hemoglobin. This condition is referred to as beta-thalassemia (BT). The present treatment strategies primarily target the correction of defective erythropoiesis, with a particular emphasis on gene therapy and hematopoietic stem cell transplantation. However, the presence of inefficient erythropoiesis in BT bone marrow (BM) is likely to disturb the previously functioning BM microenvironment. This includes accumulation of various macromolecules, damage to hematopoietic function, destruction of bone cell production and damage to osteoblast(OBs), and so on. In addition, the changes of BT BM microenvironment may have a certain correlation with the occurrence of hematological malignancies. Correction of the microenvironment can be achieved through treatments such as iron chelation, antioxidants, hypoglycemia, and biologics. Hence, This review describes damage in the BT BM microenvironment and some potential remedies.